Existence of Replica-Symmetry Breaking in Quantum Glasses - Leschke, Hajo; Manai, Chokri; Ruder, Rainer; Warzel, Simone (Physical Review Letters, 2021)
By controlling quantum fluctuations via the Falk-Bruch inequality we give the first rigorous argument for the existence of a spin-glass phase in the quantum Sherrington-Kirkpatrick model with a "transverse"magnetic field if the temperature and the field are sufficiently low. The argument also applies to the generalization of the model with multispin interactions, sometimes dubbed as the transverse p-spin model.
CRIS-Team Scopus Importer:2021-11-26